A simple non-invasive method to collect soft tick saliva reveals differences in Ornithodoros moubata saliva composition between ticks infected and uninfected with Borrelia duttonii spirochetes - Filatov, Serhii; Dyčka, Filip; Sterba, Jan; Rego, Ryan O.M. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: We developed a new simple method to assess the composition of proteinaceous components in the saliva of Ornithodoros moubata, the main vehicle for pathogen transmission and a likely source of bioactive molecules acting at the tick-vertebrate host interface. To collect naturally expectorated saliva from the ticks we employed an artificial membrane feeding technique using a simple, chemically defined diet containing phagostimulants and submitted native saliva samples collected in this way for liquid chromatography-mass spectrometry (LC-MS) analysis. These experiments were conducted with groups of uninfected ticks as well as with O. moubata infected with B. duttonii. The ticks exhibited a fair feeding response to the tested diet with engorgement rates reaching as high as 60-100% of ticks per feeding chamber. The LC-MS analysis identified a total of 17 and 15 proteins in saliva samples from the uninfected and infected O. moubata nymphs, respectively. Importantly, the analysis was sensitive enough to detect up to 9 different proteins in the samples of saliva containing diet upon which as few as 6 nymphal ticks fed during the experiments. Some of the proteins recognized in the analysis are well known for their immunomodulatory activity in a vertebrate host, whereas others are primarily thought of as structural or “housekeeping” proteins and their finding in the naturally expectorated tick saliva confirms that they can be secreted and might serve some functions at the tick-host interface. Most notably, some of the proteins that have long been suspected for their importance in the vector-pathogen interactions of Borrelia spirochetes were detected only in the samples from infected ticks, suggesting that their expression was altered by the persistent colonization of the tick’s salivary glands by spirochetes. The simple method described herein is an important addition to the toolbox available to study the vector-host-pathogen interactions in the rapidly feeding soft ticks.